Helminths of the Hydromyini (Muridae: Hydromyinae) from Papua New Guinea with the description of a new species of Labiobulura (Nematoda: Ascaridida) - Smales, Lesley R. (Zootaxa, 2006)
From a survey of helminths of the alimentary tracts of 26 hydromyins; 11 Leptomys, 1 Mayermys, 3 Neohydromys, 9 Paraleptomys, and 2 Parahydromys from Papua New Guinea an acanthocephalan, Porrorchis hydromuris; a cestode, Mathevotaenia sp.; the trematodes, Brachylaima sp., and a psilostome; and the nematodes, Heterakis fieldingi, Odilia mackerrasae, O, emanuelae, Protospirura kaindiensis, Rictularia mackerrasae, and Capillaria sp. s.l., as well as encapsulated larval ascaridids were found. All represent new host records. Labiobulura leptomyidis n. sp. (Subuluridae), differs from its congener in having longer spicules, no spines on the chordal lobes of the buccal cavity and it is described from Leptomys spp. Spirurida or Ascaridida were the dominant taxa in each helminth assemblage, with dietary preferences being a determinant. Either coevolution and or host switching, sometimes associated with migration between Australia and Papua New Guinea, also appear to have influenced the development of the helminth assemblage in each host taxon.